Designing accessible MOOCs to expand educational opportunities for persons with cognitive impairments. Issue 11 (18th August 2021) - Cinquin, Pierre-Antoine; Guitton, Pascal; Sauzéon, Hélène
ABSTRACT: Despite the promotion of equal access to education, the proportion of persons with disabilities decreases drastically from primary school to higher education, resulting in a lower level of education. This lack of qualification represents an additional obstacle to employment opportunities, reinforcing their exclusion from the social sphere. In recent years, computer-based approaches to education have undergone a real revolution, as reflected by the massive growth of MOOCs platforms. As they are flexible enough, they could provide a real opportunity to create learning environments that are beneficial to persons with disabilities. Unfortunately, most MOOCs are not 'sufficiently' accessible, especially for persons with cognitive impairments and limited learning capacities. In this article, we describe the results of a participatory design process that involved students with cognitive impairments and specialists from various fields of expertise and led to the co-design of new functionalities to enhance the accessibility of a MOOC player. We also present the results of a multiple-cases study evaluation of a first prototype, whose results support the positive impact of our design decisions. Finally, we propose an integrative framework for the design of accessible e-learning systems derived from the different needs and guidelines that emerged during the process.